ANALISIS PERANGKAT PEMBELAJARAN TEMATIK DENGAN PENDEKATAN SAINTIFIK DALAM MASA COVID-19 DI KELAS IV SD - Nurwinda Mayang Sari; Tahmid Sabri; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The purpose to describe Thematic Learning Device Analysis With Scientific Approach In Covid-19 Pandemic period in Grade IV. The method in this study is a descriptive method with a qualitative. In the study is Guru. Data collection instruments in the study are Non Participan, in-depth interviews, documentation studies, and triangulation. Data triangulation is done in two ways, namely source triangulation and triangulation method. The results showed that in planning learning to compile rpp teachers first review the syllabus, KD, defense measures, and assessments in the teacher's book then increase or decrease the indicators by addressing activity student book. Rpp and syllabus created by teachers already contain components that must be present in rpp school identity, classroom/semester, theme identity, subtheme, allocation of time, core competencies, basic competencies, indicators, objectives, methods, media, tools, learning resources, and defense measures, but basically even in the period of covid-19 RPP should be re-adjusted in this pandemic period. In carrying out learning teachers carry out online learning using whatsapp and zoom apps. The teacher's penialain is just knowledge. Keywords : Analysis, Approach, Scientific, Thematic Learning.